DEVELOPMENT MODEL FOR REMOVAL TOTAL IRON IN â€œGAMBUT WATERâ€ FOR DRINKING WATER - Sutrisno -; Elizabeth Tjahjadarmawan; Fifi - (Jurnal Riset Kimia, 2008)
ABSTRACT This research is focused on characterization of activated carbon from solid waste CPO industries and applying for treatments of gambut water for iron removal in aqueous media. Key parameters in the present study include TSS, DO, pH and total phenol is also determinated. Methods of sampling and analytical techniques for measuring key parameters are by using extended method. The small model has been developed by combining of the composting and adsorption technology. The coagulant material such as filter alum, soda caustic, and calcium hypochlorite in any ratios are varied and the optimum condition is achieved. The activated carbon is used as adsorbent by using column model. The overall results show that after coagulation and adsorption processes the total iron, TSS, DO and pH are under threshold levels (Indonesian Regulation) and suitable for drinking water meanwhile other parameters are still uncovered in this investigation. Tentatively, it can be concluded that the proposed gambit water design has achieved the optimum condition. A further study on the improvement of the treatment design and service time for adsorption process is still in progress. Keywords : total iron, gambut water, activated carbon, combining model.